The Waiting time for patients with a destination in the Outpatient Unit of Puskesmas I, South Denpasar: Waiting time for patients with a destination in the Outpatient Unit of Puskesmas I, South Denpasar - Yulia Adiningsih (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
Waiting time is a problem that often causes complaints from patients in several health facilities, one of which is the public health centre. Consistently long waiting times can lead to patient dissatisfaction. The length of waiting time has a great influence on patients on their level of satisfaction because it is related to the quality of service or treatment so that it must be considered by policy makers. The purpose of this study was to determine the characteristics of respondents, length of time and patient satisfaction in the Outpatient Unit of Puskesmas I South Denpasar. This type of research is descriptive with a quantitative approach with the sample technique used is purposive sampling. The instrument used is a questionnaire using the dimensions of tangible, responsiveness, assurance, empathy and reliability. The results of this study indicate that most of the patients said the waiting time was not long and the patients were satisfied with the services at the outpatient unit of Puskesmas I South Denpasar.